IMPLEMENTASI TUJUAN KE-2 SUSTAINABLE DEVELOPMENT GOALS (SDGS) DALAM MENGATASI PERMASALAHAN STUNTING DI KABUPATEN KUTAI TIMUR - Lumban Tobing, Evangelystha; Kusuma, Aji Ratna; Daryono, Daryono (Jurnal Academia Praja, 2025)
The purpose of this study is to explain and analyze the implementation, impact and inhibiting factors in overcoming stunting problems in East Kutai Regency. This research was conducted in Sangatta. The research method used descriptive qualitative research, namely data collection through observation, interviews, documentation, and literature research. Data analysis used interactive modeling data analysis techniques in the form of data collection, data condensation, data presentation, and conclusion drawing and verification. The results showed that the implementation of the 2nd goal of the Sustainable Development Goals (SDGs) in overcoming the problem of stunting in East Kutai Regency has been implemented very well. The stunting prevalence rate in East Kutai Regency has decreased to 16.4%. Seminars, campaigns and the use of applications are used to maximize the achievement of policy implementation. The limited human resources are still an obstacle, while the budget resources have no significant obstacles. The disposition carried out by all parties involved has been running well and in accordance with standard operating procedures (SOPs) and is carried out with full responsibility in accordance with their respective tasks and functions. So, based on the research that has been done, communication is still the biggest inhibiting factor in the implementation of this policy. The implementation of the 2nd goal of the Sustainable Development Goals (SDGs) in overcoming the problem of stunting in East Kutai Regency has been well implemented but not optimal.